Empowerment of MSME Owners Through Assistance in Obtaining NPWP in Lawe-Lawe, Penajam: Pemberdayaan Pelaku UMKM Melalui Pendampingan Pembuatan NPWP di Lawe-Lawe, Penajam - Boer, Kheyene; Agustin Rachmat, Andini (Dharmahita: Journal of Community Service and Development, 2024)
The socialization and assistance activities for obtaining NPWP (Taxpayer Identification Number) were conducted on July 22 and August 1, 2023, at MSME outlets in Lawe-Lawe Village, Penajam District, Penajam Paser Utara Regency, East Kalimantan. Focusing on two MSME owners, the activity aimed to provide knowledge on taxation rights and obligations, the benefits of having an NPWP, and the requirements for obtaining one. The activity involved two stages: a survey and the implementation. Findings revealed that MSME owners had not registered as taxpayers due to limited knowledge about NPWP registration procedures and requirements. The expected outcome is to educate MSME owners on fulfilling tax obligations properly. Addressing the main issue of the lack of understanding about the importance and benefits of having an NPWP, the solution involved detailed explanations of NPWP, basic tax regulations, applicable rates, and the advantages of holding an NPWP. This assistance aims to equip MSME owners with comprehensive knowledge on NPWP, highlighting the need for self-awareness in legalizing their businesses and complying with tax obligations.